2023
DOI: 10.1055/a-2146-6879
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Effect of Different Organ Metastasis on the Prognosis of NSCLC

Abstract: Objective: The aim of this study was to explore the effect of different organ metastasis on the prognosis of NSCLC. Methods: Patients with distant metastatic NSCLC were selected from Surveillance, Epidemiology, and End Results (SEER) database during 2016-2019. The incidence of different organ metastasis and their association with clinicopathological factors were explored. Overall survival (OS) and lung cancer-specific survival (LCSS) for metastatic NSCLC were calculated and multivariate Cox regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…As distant metastasis contributes to a large portion of NSCLC-related death, the prognosis of metastatic NSCLC patients remains dismal ( 4 ). Although sites of distant metastases are equivalent in the American Joint Committee on Cancer (AJCC) stage system, previous studies revealed that the survival of patients varies with sites of metastases ( 5 - 7 ). Further, liver metastasis (LM) is the most lethal site compared with other metastatic lesions, with a median survival of only 3–5 months ( 5 , 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…As distant metastasis contributes to a large portion of NSCLC-related death, the prognosis of metastatic NSCLC patients remains dismal ( 4 ). Although sites of distant metastases are equivalent in the American Joint Committee on Cancer (AJCC) stage system, previous studies revealed that the survival of patients varies with sites of metastases ( 5 - 7 ). Further, liver metastasis (LM) is the most lethal site compared with other metastatic lesions, with a median survival of only 3–5 months ( 5 , 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%